Molecular Weight Determination of L-asparaginase from Bacillus licheniformis - Daifallah, Vivian Ramzi; Yazji, Sabah Nassib; Al-Amir, Lina Abdulkarim (Journal of agricultural, environmental and veterinary sciences, 2024)
Due to the nutritional and pharmaceutical application importance of the asparaginase enzyme and the lack of commercial availability of the enzyme in local markets, the study focused on producing the asparaginase enzyme from Bacillus bacteria and purifying it for the possibility of its application in the food industries. Purification steps of asparaginase produced by Bacillus licheniformis started by precipitation with 80% acetone, then separation by column chromatography using Sephadex G-100 and Sephacryl DEAE-sepharose. The molecular weight was 34.4 kDa determined using SDS PAGE.